SOSIALISASI EDUKATIF TENTANG GIZI SEIMBANG UNTUK PENDERITA DIABETES MELLITUS DI KABUPATEN TUBAN - Lilia Faridatul Fauziah; Nikita Welandha Prasiwi; Mohammad Zainul Ma'arif (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2021)
Diabetes Mellitus is a non-communicable disease that causes an increase in mortality. The prevalence in Tuban Regency is 1.7%, cases of diabetes mellitus are increasing. One of the risk factors for diabetes mellitus is unbalanced eating habits. In addition, physical activity is a major risk factor in triggering the occurrence of Diabetes Mellitus. These counseling and exercise activities aim to increase knowledge and awareness related to balanced diet and diabetes mellitus. In this activity, all participants were active in the discussion that was held after the counseling. In addition, all participants were enthusiastic in participating in joint gymnastics activities. It is hoped that after this community service activity all participants can apply a healthy lifestyle and balanced diet in their daily life. In addition, it also controls blood glucose levels and nutritional status to keep it normal and ideal. Keywords: Balanced Diet, Nutrition Counseling, Gymnastics, Diabetes mellitus